ORGANIZATION OF SELF-DEPENDENT COGNITIVE ACTIVITY OF PUPILS IN PHYSICS USING INFORMATION TECHNOLOGIES. - V. D. Sharko; A.O. Solodovnik (Kherson State University, 2010)
The article deals with opportunities of using information technologies to organize self-dependent cognitive activity of pupils in physics.